A New Method of Legal Reasoning in the Ḥanafī School: Intra Madhhab Talfīq - Burak Ergin (İslam Tetkikleri Dergisi)
Legal reasoning in the Ḥanafī School happened using various methods such as qiyas [analogy], istihsan [consideration of juristic preference], and takhrīj [deduction]. Another method is intra-madhhab talfıq [amalgamation]. Intramadhhab talfīq involves the creation of a new view by combining the views of two scholars within the same madhhab who’d expressed opposing views to one another. As stated in the relevant literature, intra-madhhab talfīq was used by the chief qadi of Damascus Tarsūsī in the 14th century as a method of legal reasoning. Qāsim b. Qatlūbaghā, who lived a century after Tarsūsī, criticized some muftis who proclaimed fatwās using talfīq as a method of legal reasoning, stating talfīq to be an invalid legal method. As for the 16th century, Shelebī and Ibn Nujaym used talfīq similar to Tarsūsī to solve certain issues related to endowments. By the 17th century, two jurists of the period, Shurunbulālī and Ibn Bīrī, touched upon this issue deeply in the treatises they wrote on the subject of moving from one madhab to another and talfīq. Both scholars objected to talfīq, stated this method to be unusable for solving fiqh issues. Another Ḥanafī scholar, Ibn ‘Ābidīn, tried to distinguish between intra-madhhab and inter-madhab. Therefore, this study examines the historical course of the debates on whether or not intra-madhhab talfiq is a usable method of jurisprudence with respect to the Ḥanafī School as well as its status during the Ottoman era.